Nonlinear optics - Boyd, Robert W., 1948- (Academic Press, 1992)
Nonlinear Optics is an advanced textbook for courses dealing with nonlinear optics, quantum electronics, laser physics, contemporary and quantum optics, and electrooptics. Its pedagogical emphasis is on fundamentals rather than particular, transitory applications. As a result, this textbook will have lasting appeal to a wide audience of electrical engineering, physics, and optics students, as well as those in related fields such as materials science and chemistry. Key Features* The origin of optical nonlinearities, including dependence on the polarization of light* A detailed treatment of the q.